Impact of dietary enzyme complex on growth performance, nutrient digestibility and fecal noxious gas emissions in growing pigs - ZHAO, P Y; LI, T S; KIM, I H (The Indian Journal of Animal Sciences, 2016)
Growing pigs (180, Yorkshire-Landrace × Duroc) with an average body weight (BW) of 26.40 ± 2.29 kg were used in a 6-week study to evaluate the effect of dietary enzyme complex on growth performance, nutrient digestibility, and fecal noxious gas emission in growing pigs. Pigs were sorted by their initial BW and sex, and allotted to pen given a basal diet with 0, 0.05 and 0.10% enzyme complex. Overall (d 0 to 36), pigs fed the enzyme complex supplementation diets had a greater apparent total tract digestibility (ATTD) of dry matter (DM) and nitrogen (N) than pigs fed the basal diet (CON). Fecal ammonia, hydrogen sulfide, total mercaptans, and acetic acid emissions were not affected by the enzyme complex supplementation on d 1, 3, 5, and 7. No effects were observed on growth performance, nutrient digestibility, and fecal noxious gas emissions between the enzyme complex supplementation treatments. In conclusion, enzyme complex supplementation in corn-soybean based diets improved the ATTD of DM and N, but neither improved growth performance nor decreased fecal noxious gas emissions in growing pigs.